"Free Money" of Large Manufacturing Corporations and the Rate of Interest: A Reply - Kisselgoff, Avram (Econometrica, 1946)
The note by Professor Duncan is chiefly an elaboration of the qualification presented without ambiguity in the concluding section of my study of corporate cash balances.' However, one point that has been made by Professor Duncan requires clarification. If correlation coefficients and trend lines are laid aside Professor Duncan recognized that from 1935 to 1937 the data verify the liquiditypreference theory. It is evident, however, from the analysis of the series involved that the accumulation of which began in 1929 reached its peak in 1932 and decreased to its lowest point in 1937; but at that low point it still formed 20 per cent of cash balances. During this period (1929-37) the falling volume of marketable securities held by large manufacturing corporations was negatively correlated with rising prices of U. S. Government bonds without exception for each year. The liquidation of marketable securities during the thirties, at a time when there was free money, undoubtedly reflects the liquidity preference of the corporations which joined in the thirties the bear brigade, to use Keynes's expression. Therefore, the singling out of data for 1935-37 is arbitrary. In addition, Professor Duncan's calculations for this period are incomplete inasmuch as they do not take into account the rate of profit which reflects the business expectations of the corporations. Indeed, the actual volume of idle money is the combined result of the sales of marketable securities and the amount of money released or absorbed by the transaction sphere of large manufacturing corporations. The accumulation of idle money in the thirties should, therefore, be explained by the rate of profit and the rate of interest simultaneously, and that explanation can be achieved only by the use of the multiple-correlation technique.